3(x-1)-(2x-4)=1
Me ajudem
Soluções para a tarefa
Respondido por
5
Oi
3(x-1)-(2x-4)=1
3(x-1)-2x+4=1
3x-3-2x+4=1
x-3+4=1
x+1=1
x=1-1
![\boxed{\boxed{\boxed{x=0}}} \boxed{\boxed{\boxed{x=0}}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cboxed%7B%5Cboxed%7Bx%3D0%7D%7D%7D)
3(x-1)-(2x-4)=1
3(x-1)-2x+4=1
3x-3-2x+4=1
x-3+4=1
x+1=1
x=1-1
Thaimaurente:
Muito obrigada
Perguntas interessantes
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
História,
1 ano atrás
Inglês,
1 ano atrás
Matemática,
1 ano atrás